JOB CRAFTING SEBAGAI PREDIKTOR WORK ENGAGEMENT PADA KARYAWAN DI PERUSAHAAN PT. SAMINDO UTAMA KALTIM - Yeltin, Yeltin; Sutarto Wijono (Bajang Institute, 2025)
This research was motivated by the importance of work engagement as a factor that influences employee performance and productivity. One factor considered to play a role in enhancing work engagement is job crafting, namely employees’ proactive efforts to adjust their tasks, relationships, and perspectives toward work. The aim of this study was to examine whether job crafting can serve as a predictor of work engagement among employees at PT. Samindo Utama Kaltim. This research employed a quantitative method with a correlational design. The participants consisted of 150 permanent employees who had worked for at least one year, selected using purposive sampling. The research instruments were the job crafting scale and the work engagement scale, both completed online by the participants. Data were analyzed using Pearson correlation and simple linear regression. The results indicated that job crafting is a positive and significant predictor of work engagement, with a contribution of 12%. These findings suggest that employees who engage more actively in job crafting tend to experience higher levels of work engagement. The implication of this study highlights the importance for companies to encourage employees to engage in job crafting by providing work flexibility, opportunities for self-development, and organizational support in order to further enhance work engagement